Localization of acyl carrier protein in Escherichia coli. - Jackowski, S (1985)
Acyl carrier protein was localized by immunoelectron microscopy in the cytoplasm of Escherichia coli. These data are inconsistent with the previous report of an association between acyl carrier protein and the inner membrane (H. Van den Bosch, J.R. Williamson, and P.R. Vagelos, Nature [London] 228:338-341, 1970). Moreover, bacterial membranes did not bind a significant amount of acyl carrier protein or its thioesters in vitro. A thioesterase activity specific for long-chain acyl-acyl carrier protein was associated with the inner membrane.